Childbirth evacuation among rural and remote Indigenous communities in Canada: A scoping review. Issue 1 (February 2022) - Silver, Hilah; Sarmiento, Ivan; Pimentel, Juan-Pablo; Budgell, Richard; Cockcroft, Anne; Vang, Zoua M.; Andersson, Neil
Abstract: Problem: Routine evacuation of pregnant Indigenous women from remote regions to urban centres for childbirth is a central strategy for addressing maternal health disparities in Canada. Maternal evacuation continues despite mounting evidence of its negative impacts on Indigenous women and families. Background: Since the 1960s, pregnant Indigenous women living in remote regions in Canada have been transferred to urban hospitals for childbirth. In the following decades, evidence emerged linking maternal evacuation with negative impacts on Indigenous women, their families, and communities. In some communities, resistance to evacuation and the creation of local birthing facilities has resulted in highly diverse experiences of childbirth and evacuation. Aim: A scoping review mapped the evidence on maternal evacuation of Indigenous women in Canada and its associated factors and outcomes from 1978 to 2019. Methods: We searched MEDLINE, Embase, and CINAHL, and grey literature from governmental and Indigenous organizations. We collated the evidence on maternal evacuation into 12 themes. Results: Factors related to evacuation include (a) evacuation policies (b) institutional coercion (c) remoteness and (d) maternal-fetal health status. Evacuation-related outcomes include (e) maternal-child health impacts (f) women's experience of evacuation (g) financial hardships (h) family disruption (i) cultural continuity and community wellness (ij) engagement with health services (k) self-determination, and (l) quality of health services. Discussion: Numerous emotional, social and cultural harms are associated with evacuation of Indigenous women in Canada. Little is known about the long-term impacts of evacuation on Indigenous maternal-infant health. Evidence on evacuation from remote Métis communities remains a critical knowledge gap.